Electrical component ignition in a closed enclosure adjacent to a controlled fire. (10th December 2019) - Zavaleta, Pascal; Bouygues, Olivier; Lapuerta, Céline
Summary: Electrical cabinet fires are one of the main fire hazards in nuclear power plants (NPPs). The electrical cabinets are often arranged in rows of adjacent cabinets (ACs) in NPPs. So the ability of a cabinet fire to spread to ACs is a major concern for fire safety. This work aims to investigate the impact on the fire spread of the air gap between two electrical cabinets, the electrical component type contained in the AC, and its ventilation mode. For that purpose, a test device composed of two adjacent steel enclosures was designed in order to reproduce at reduced‐scale adjacent electrical cabinets. This study first reveals that the studied electrical component types spontaneously ignited when their temperature and the incident heat flux reach critical ignition values. These ignition criteria are assessed for each component type. The tests also show that the air gap increase slows down the rise of the side wall temperature of the two enclosures, which delays the ignition time of the electrical components. This work finally highlights that the mechanical ventilation of the adjacent enclosure (AE) has an impact on the ignition conditions. In contrast, the natural ventilation as implemented in the AE has a small effect on these conditions.